Measurement of the semileptonic $ t\overline{t} $ + γ production cross section in pp collisions at $ \sqrt{s}=8 $ TeV - CMS collaboration (2230 authors) (2017)
A measurement of the cross section for top quark-antiquark ( $ t\overline{t} $ ) pairs produced in association with a photon in proton-proton collisions at $ \sqrt{s}=8 $ TeV is presented. The analysis uses data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 19.7 fb$^{1}$. The signal is defined as the production of a $ t\overline{t} $ pair in association with a photon having a transverse energy larger than 25 GeV and an absolute pseudorapidity smaller than 1.44. The measurement is performed in the fiducial phase space corresponding to the semileptonic decay chain of the $ t\overline{t} $ pair, and the cross section is measured relative to the inclusive $ t\overline{t} $ pair production cross section. The fiducial cross section for associated $ t\overline{t} $ pair and photon production is found to be 127 ±27 (stat+syst) fb per semileptonic final state. The measured value is in agreement with the theoretical prediction.